Footprint lesion: a mirror image of an endometrial polyp - Shah, Nitin H.; Joshi, Aditi V.; Mourya, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Endometrial polyps may present with a variety of symptomatology. They are mostly benign and commonly encountered in the reproductive age group. Hysteroscopy is an emerging tool for diagnostic as well as a therapeutic purposes. We report a case of endometrial polyp diagnosed on hysteroscopy, with a “footprint”, that is contact lesion visible. This is a relatively rare phenomenon, and there is sparse information and literature regarding this entity. Hence the true nature of its effects is yet unknown.